Biocontrol potential of Bacillus velezensis EM-1 associated with suppressive rhizosphere soil microbes against tobacco bacterial wilt - Sui, Xiaona; Han, Xiaobin; Cao, Jianmin; Li, Yiqiang; Yuan, Yuan; Gou, Jianyu; Zheng, Yanfen; Meng, Chen; Zhang, Chengsheng (Frontiers in Microbiology, 2022)
Tobacco bacterial wilt caused by Ralstonia solanacearum is one of the most devastating diseases. Microbial keystone taxa were proposed as promising targets in plant disease control. In this study, we obtained an antagonistic Bacillus isolate EM-1 from bacterial wilt suppressive soil, and it was considered as rhizosphere resident bacteria based on high (100%) 16S rRNA gene similarity to sequences derived from high-throughput amplicon sequencing. According to 16S rRNA gene sequence and MLSA analysis, strain EM-1 was identified as Bacillus velezensis. This strain could inhibit the growth of R. solanacearum, reduce the colonization of R. solanacearum in tobacco roots, and decrease the incidence of bacterial wilt disease. In addition, strain EM-1 also showed strong inhibitory effect on other phytopathogens such as Alternaria alternata, Phytophthora nicotianae, etc., indicating a wide antagonistic spectrum. The antimicrobial ability of EM-1 can be attributed to its volatile, lipopeptide and polyketide metabolites. Iturin A (C14, C15 and C16) were the main lipopeptides, macrolactin A and macrolactin W were the main polyketides in fermentation broth of EM-1, while heptanone and its derivatives were dominant in the volatile. Among them, heptanones and macrolactins but not iturins might be the main potential antibacterial substances. Complete genome sequencing was performed and the biosynthetic gene clusters responsible for iturin A and macrolactin were identified. Moreover, strain EM-1 can also induce plant resistance by increasing the activity of CAT and PPO in tobacco. These results indicated that EM-1 can be served as biocontrol Bacillus strain for tobacco bacterial wilt control. This study also provided a better insight into the strategy of exploring biocontrol agent based on rhizosphere microbiome.